2021
DOI: 10.1007/s00384-021-03986-8
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient cannot discriminate metastatic and non-metastatic lymph nodes in rectal cancer: a meta-analysis

Abstract: Background Our aim was to provide data regarding use of diffusion-weighted imaging (DWI) for distinguishing metastatic and non-metastatic lymph nodes (LN) in rectal cancer. Methods MEDLINE library, EMBASE, and SCOPUS database were screened for associations between DWI and metastatic and non-metastatic LN in rectal cancer up to February 2021. Overall, 9 studies were included into the analysis. Number, mean value, and standard deviation of DWI parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Two studies reported that ADC could not be measured in a subset of 21-27% of the visible LN due to their small dimensions or local image distortions [76,77]; other studies excluded the LN <2mm because delineations were technically too challenging [84,85]. However, technical factors such as different scanner technology, b-values, different ADC calculations, and field strength represent the main drawback for the definition of an effective and robust threshold for ADC maps (Figures 2 and 3) [86,87]. Chen et al performed another kind of quantitative analysis.…”
Section: Advanced Mri Techniques: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%
“…Two studies reported that ADC could not be measured in a subset of 21-27% of the visible LN due to their small dimensions or local image distortions [76,77]; other studies excluded the LN <2mm because delineations were technically too challenging [84,85]. However, technical factors such as different scanner technology, b-values, different ADC calculations, and field strength represent the main drawback for the definition of an effective and robust threshold for ADC maps (Figures 2 and 3) [86,87]. Chen et al performed another kind of quantitative analysis.…”
Section: Advanced Mri Techniques: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) as a DW-MRIderived parameter was shown to correlate negatively with tumour cellularity in different solid cancers [6]. Results of accumulating meta-analyses showed that the ADC value, depending on cancer type [7][8][9], could distinguish benign from malignant lesions [10][11][12], predict response to treatment [13,14], and determine the expression of tumour biomarkers [15,16]. However, there are few studies investigating the diagnostic accuracy of ADC for differentiating lymphomas from other malignant tumours.…”
Section: Introductionmentioning
confidence: 99%